A clinical update on posttraumatic stress disorder in burn injury survivors. (August 2017) - McLean, Loyola; Chen, Runsen; Kwiet, Julia; Streimer, Jeffrey; Vandervord, John; Kornhaber, Rachel
Objectives: Burn injuries are complex traumatic events carrying high risks of acute physical and psychosocial morbidity. With greater survival, clinical and research attention has turned to psychosocial recovery outcomes and risk factors. It is timely to summarise current issues in posttraumatic disorders after burn injury for mental health and integrative care clinicians. Posttraumatic stress disorder (PTSD) is a common outcome of severe burn injury. There are difficulties in delivering current best practice treatments to many survivors especially those in rural and remote areas and those with comorbidities. Vicarious traumatization of clinicians, families and carers requires attention and internationally there are moves to psychosocial screening and outcome tracking. Conclusions: The role of the multidisciplinary treatment, integrated and trauma-informed care is essential. While level 1 evidence for PTSD treatments theoretically applies, adaptations that consider comorbidities and treatment contexts are often essential with further research required.